Measurement of reactive oxygen intermediate production in haemocytes of the penaeid shrimp, penaeus vannamei - Muñoz (2000)
Measurement of reactive oxygen intermediate production in Haemocytes of the Penaeid shrimp, Penaeus Vannamei